Multidirectional chromosome painting substantiates the occurrence of extensive genomic reshuffling within Accipitriformes. (December 2015) - Nie, Wenhui; O'Brien, Patricia; Fu, Beiyuan; Wang, Jinghuan; Su, Weiting; He, Kai; Bed'Hom, Bertrand; Volobouev, Vitaly; Ferguson-Smith, Malcolm; Dobigny, Gauthier; Yang, Fengtang
Abstract Background Previous cross-species painting studies with probes from chicken (Gallus gallus ) chromosomes 1–10 and a paint pool of nineteen microchromosomes have revealed that the drastic karyotypic reorganization in Accipitridae is due to extensive synteny disruptions and associations. However, the number of synteny association events and identities of microchromosomes involved in such synteny associations remain undefined, due to the lack of paint probes derived from individual chicken microchromosomes. Moreover, no genome-wide homology map between Accipitridae species and other avian species with atypical karyotype organization has been reported till now, and the karyotype evolution within Accipitriformes remains unclear. Results To delineate the synteny-conserved segments in Accipitridae, a set of painting probes for the griffon vulture, Gyps fulvus (2n = 66) was generated from flow-sorted chromosomes. Together with previous generated probes from the stone curlew, Burhinus oedicnemus (2n = 42), a Charadriiformes species with atypical karyotype organization, we conducted multidirectional chromosome painting, including reciprocal chromosome painting betweenB. oedicnemus andG. fulvus and cross-species chromosome painting betweenB. oedicnemus and two accipitrid species (the Himalayan griffon, G. himalayensis 2n = 66, and the common buzzard, Buteo buteo, 2n = 68). In doing so, genome-wide homology maps betweenB. oedicnemus and three Accipitridae species were established. From there, a cladistic analysis using chromosomal characters and mapping of chromosomal changes on a consensus molecular phylogeny were conducted in order to search for cytogenetic signatures for different lineages within Accipitriformes. Conclusion Our study confirmed that the genomes of the diurnal birds of prey, especially the genomes of species in Accipitriformes excluding Cathartidae, have been extensively reshuffled when compared to other bird lineages. The chromosomal rearrangements involved include both fusions and fissions. Our chromosome painting data indicated that the Palearctic common buzzard (BBU) shared several common chromosomal rearrangements with some Old World vultures, and was found to be more closely related to other Accipitridae than to Neotropical buteonine raptors from the karyotypic perspective. Using both a chromosome-based cladistic analysis as well as by mapping of chromosomal differences onto a molecular-based phylogenetic tree, we revealed a number of potential cytogenetic signatures that support the clade of Pandionidae (PHA) + Accipitridae. In addition, our cladistic analysis using chromosomal characters appears to support the placement of osprey (PHA) in Accipitridae.